(untitled) (Current Horticulture, 2024)
A field experiment was conducted at CCS Haryana Agricultural University, RRS, Bawal (Rewari), Haryana, on 13 genotypes (4 tall double-seeded, 6 tall single-seeded, 3 dwarf-single seeded) of phalsa having a wide range of variability in flowering and fruiting traits in randomized block design, during 2018-19. The number of flowers/ inflorescence varied from 3 to 4 in Bawal Phalsa 1, Bawal Phalsa 2, Bawal Phalsa 3, Bawal Phalsa 4, Bawal Phalsa 5, Bawal Phalsa 6, Bawal Phalsa 7, Bawal Phalsa 8, Bawal Phalsa 9 and Bawal Phalsa 10. However, 2 to 5 flowers/ inflorescence were observed in dwarf germplasm. Early flowering was found in tall double-seeded germplasm, whereas end of flowering and fruit maturity exhibited early in dwarf germplasm. The fruit length, breadth, and weight were maximum in Bawal Phalsa 4, minimum in Bawal Phalsa 12, whereas number of fruits picking were maximum in Bawal Phalsa 5 and minimum in Bawal Phalsa 1. Fruit shape was globose type in Bawal Phalsa 1, Bawal Phalsa 2, Bawal Phalsa 3 and Bawal Phalsa 4, whereas round in Bawal Phalsa 5, Bawal Phalsa 6, Bawal Phalsa 7, Bawal Phalsa 8, Bawal Phalsa 9, Bawal Phalsa 10 and dwarf germplasm. Fruit skin colour was purple in tall double-seeded, whereas deep purple in tall single-seeded and dwarf germplasm. Fruit lobe was present only in tall double-seeded germplasm. Inflorscence type and petal colour showed no variation.